Peran Pendidikan Kewarganegaraan Dalam Mengembangkan Moral dan Sosial Siswa Sekolah Dasar - Melyana Indiarsih; Rahman Wahid (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2024)
The decline in moral values ​​and the social decline of the current generation, especially at the elementary school level, is one of the problems in the world of education. With the role of citizenship education as a subject in elementary school, it is hoped that it can develop students' moral and social skills. The method used in this research is a literature review collected from various reference sources, both journals and books. From the reference data collected, the data is then analyzed and reduced and then the data is concluded. Through a study of the role of citizenship education, it is hoped that it can provide insight for educators so that they can participate optimally in developing children's moral and social development, so that students' moral problems can be reduced or even very minimal and students' social development can be realized as it should be.